2021
DOI: 10.3390/info12050192
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of eWOM Antecedents on Online Purchase Intention in China

Abstract: Drawing on social identity theory, this study aims to examine the impact of antecedents of eWOM on the online purchase intention (OPI) of fashion-related products. In addition, social media usage moderates the relationship between eWOM and OPI. A structured questionnaire was completed by a sample of 477 Chinese WeChat users. An online survey was conducted in two metropolitan cities (Beijing and Shanghai). The hypotheses were tested using structural equation modeling (SEM) generated by AMOS 22. The findings of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…Influencers carry out a meaning transfer process that stimulates interest and influences consumers' attitudes toward products or brands and purchases [3]. E-word of mouth (E-WOM) is more effective when carried out by recognized personalities with a greater impact on online consumers' purchase intention [4,5]. The extant literature recognizes that influencer marketing contributes to consumer purchase intention [2,6,7], and that fashion consumers are highly influenced by trends, which are conveyed by fashion influencers, namely through social media [8]; therefore, the fashion industry has strongly considered and used FIs [9].…”
Section: Fashion Influencersmentioning
confidence: 99%
“…Influencers carry out a meaning transfer process that stimulates interest and influences consumers' attitudes toward products or brands and purchases [3]. E-word of mouth (E-WOM) is more effective when carried out by recognized personalities with a greater impact on online consumers' purchase intention [4,5]. The extant literature recognizes that influencer marketing contributes to consumer purchase intention [2,6,7], and that fashion consumers are highly influenced by trends, which are conveyed by fashion influencers, namely through social media [8]; therefore, the fashion industry has strongly considered and used FIs [9].…”
Section: Fashion Influencersmentioning
confidence: 99%
“…At that time, the role of eWOM has become very significant in obtaining information for customers' decision making process (Hussain et al, 2017). An important conclusion from this line of research is that these eWOM contents have a very significant effect on customer OPI (Filieri et al, 2018;Bilal et al, 2021b). Some studies have demonstrated that eWOM significantly influences customers' OPI.…”
Section: Electronic Word-of-mouth (Ewom)mentioning
confidence: 99%
“…The disagreement in the academic community is probably due to the particular categories of goods in previous studies, such as books [4,35,36], movies [11,26,27,33,35], digital cameras [3], software [37], video games [9,38], hotels [39][40][41][42][43], restaurants [44], and fashion products [45]. Prior studies tend to focus on the online sales of nondurable goods or product categories that involve the online consumption of digital products.…”
Section: Literature Reviewmentioning
confidence: 99%